catalyst
By adding graphite carbon nitride to the electrocatalyst material, the problem of insufficient activity and stability in the redox reaction of existing electrocatalyst materials is solved, and more efficient and economical fuel cell performance is achieved.
Patent Information
- Application Number
- JP2022540889
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-12
- Filing Date
- 2021-02-11
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2041-02-11
AI Technical Summary
Electrocatalyst materials in existing fuel cells have problems of insufficient activity and stability, especially in redox reactions, where the high cost of precious metal catalysts such as platinum and limited resources become bottlenecks.
The electrochemical properties of graphite carbon nitride are improved by applying graphite carbon nitride in the precursor of the catalyst material using catalyst materials.
The electrochemical properties of catalyst materials are significantly improved, including improving the activity and stability of redox reactions, reducing dependence on precious metal catalysts, reducing costs, and improving the overall performance of fuel cells.
Smart Images

Figure 0007663584000001 
Figure 0007663584000002 
Figure 0007663584000003
Abstract
Description
[Technical field]
[0001] The present invention provides novel catalytic materials and methods of making the materials. The catalytic materials include electrocatalysts and graphitic carbon nitride. [Background technology]
[0002] A fuel cell is an electrochemical cell that includes two electrodes separated by an electrolyte. A fuel, such as hydrogen, an alcohol such as methanol or ethanol, or formic acid, is supplied to the anode, and an oxidant, such as oxygen or air, is supplied to the cathode. Electrochemical reactions occur at the electrodes, and the chemical energy of the fuel and oxidant is converted into electrical energy and heat. Electrocatalysts are used to facilitate the electrochemical oxidation of the fuel at the anode and the electrochemical reduction of oxygen at the cathode.
[0003] Fuel cells are usually classified according to the nature of the electrolyte used. In most cases, the electrolyte is a solid polymer membrane, which is electronically insulating but ionically conductive. In proton exchange membrane fuel cells (PEMFCs), the ionically conductive membrane conducts protons, and protons produced at the anode are transported across the ionically conductive membrane to the cathode, where they combine with oxygen to form water.
[0004] The main component of a PEMFC is the membrane electrode assembly (MEA), which is essentially composed of five layers. The central layer is a polymeric ion-conducting membrane. On either side of the ion-conducting membrane are electrocatalyst layers that contain electrocatalysts designed for specific electrolysis reactions. Finally, adjacent to each electrocatalyst layer is a gas diffusion layer. The gas diffusion layers must allow reactants to reach the electrocatalyst layers and must conduct the electrical current produced by the electrochemical reactions. Therefore, the gas diffusion layers must be porous and electrically conductive.
[0005] The electrocatalyst layer also generally includes a proton conducting material, such as a proton conducting polymer, to assist in the transfer of protons from the anode electrocatalyst to the ion conducting membrane and / or from the ion conducting membrane to the cathode electrocatalyst.
[0006] Conventionally, membrane electrode assemblies can be constructed by a number of methods. Typically, the methods involve applying one or both of the electrocatalyst layers to an ion-conducting membrane to form a catalyst-coated ion-conducting membrane. A gas diffusion layer is then applied to the electrocatalyst layers. Alternatively, an electrocatalyst layer is applied to a gas diffusion layer to form a gas diffusion electrode, which is then combined with an ion-conducting membrane. A membrane electrode assembly can be made by a combination of these methods, for example, applying one electrocatalyst layer to an ion-conducting membrane to form a catalyst-coated ion-conducting membrane and applying the other electrocatalyst layer as a gas diffusion electrode.
[0007] The electrocatalyst layer generally comprises an electrocatalytic material comprising a metal or metal alloy suitable for fuel oxidation or oxygen reduction reactions, depending on whether the layer is used at the anode or cathode. Electrocatalysts for fuel oxidation and oxygen reduction are typically based on platinum or platinum alloyed with one or more other metals. Platinum or platinum alloy electrocatalysts can be in the form of unsupported nanometer-sized particles (e.g., metal black) or can be deposited as individual nanoparticles on a support material (supported electrocatalyst), resulting in very high electrocatalytic surface areas. Electrocatalysts can also be in the form of coatings or stretched films deposited on a support material. A wide range of catalytic concepts, such as Pt binary alloys, Pt monolayer electrocatalysts, Pt skin electrocatalysts, and nanostructured thin film electrocatalysts, have been investigated over the past decade. Another approach to reported high activity catalysts is that of the dealloyed Pt-M concept, i.e., materials obtained by synthesis of base metal (M)-rich particles, which are subjected to a selective leaching process of the less precious metal from the particles.
[0008] There is a continuing need for electrocatalysts, particularly oxygen reduction electrocatalysts, with improved activity and / or stability, resulting in more efficient utilization of expensive platinum electrocatalysts, which could improve the performance of membrane electrode assemblies or reduce the loading (and therefore cost) of electrocatalysts used in membrane electrode assemblies, or combine the benefits of both.
[0009] One avenue of research involves the use of graphitic carbon nitride (g-C3N4) as a support material for platinum oxygen reduction reaction electrocatalysts. In this field, M. Kim et al. in J. Mater. Chem. 2007, 17, 1656-1659 report Pt-Ru electrocatalysts for the anode of direct methanol fuel cells supported on g-C3N4. Also, H. Huang et al. in Adv. Mater. 2014, 26 5160-5165 report Pt-decorated graphene and g-C3N4 sheets useful as methanol oxidation electrocatalysts. In addition, I. Lee et al. in Appl. Catal. B: Environ. 2018, 237, 318-326 report an oxygen reduction reaction electrocatalyst comprising platinum dispersed on a support, the support having a core-shell structure in which carbon black particles are covered with sheets of g-C3N4 and containing at least 17 wt% g-C3N4. Summary of the Invention
[0010] Thus, in a first aspect, the present invention provides a method of making a catalytic material comprising, preferably consisting essentially of, more preferably consisting of (or consisting only of) electrocatalyst particles, a support material, and graphitic carbon nitride, the method comprising: (i) providing a catalyst material precursor comprising, preferably consisting essentially of, more preferably consisting of (or consisting only of) electrocatalyst particles dispersed on a support material; then (ii) applying graphitic carbon nitride to the catalytic material precursor provided in step (i).
[0011] The term "catalytic material precursor" in this sense refers to a material from which the graphitic carbon nitride-containing catalytic material of the present invention can be made. Such catalytic material precursors may have catalytic activity themselves, and may be, for example, conventional catalytic materials comprising an electrocatalyst dispersed on a support material in the absence of graphitic carbon nitride. The catalytic material precursor does not comprise graphitic carbon nitride.
[0012] In a second aspect, the present invention provides a catalytic material obtainable by the method of the first aspect of the invention.
[0013] In a third aspect, the present invention provides a catalytic material comprising, preferably consisting essentially of, more preferably consisting of (or consisting only of) electrocatalyst particles, a support material, and graphitic carbon nitride, wherein the electrocatalyst particles are dispersed on the support material, and the catalytic material comprises 5 wt% or less graphitic carbon nitride based on the total weight of the graphitic carbon nitride and the support material.
[0014] It is surprising that the catalytic material of the present invention, i.e. the catalytic material of the second or third aspect, or the catalytic material made according to the first aspect, exhibits improved electrochemical performance over conventional catalytic materials comprising an electrocatalyst dispersed on a support material, and in particular it is surprising that the electrochemical performance of such conventional catalytic materials can be improved by applying graphitic carbon nitride to the catalytic material.
[0015] The present invention also provides an electrocatalyst layer comprising the catalytic material of the present invention.
[0016] The present invention also provides a catalyst coated ion conducting membrane comprising an electrode catalyst layer of the present invention and an ion conducting membrane.
[0017] The present invention also provides a gas diffusion electrode comprising an electrode catalyst layer of the present invention and a gas diffusion layer.
[0018] The present invention also provides a membrane electrode assembly comprising the catalyst layer of the present invention, the catalyst coated ion conducting membrane of the present invention, or the gas diffusion electrode of the present invention.
[0019] The present invention also provides a fuel cell comprising the electrode catalyst layer of the present invention, the catalyst coated ion conductive membrane of the present invention, the gas diffusion electrode of the present invention, or the membrane electrode assembly of the present invention.
[0020] The present invention also provides a catalyst decal transfer substrate comprising an electrode catalyst layer of the present invention and a decal transfer substrate. [Brief description of the drawings]
[0021] [Figure 1] 1 shows an energy dispersive X-ray spectroscopy (EDS) elemental mapping image of the catalyst material of Example 1. [Diagram 2] 1 shows deconvoluted X-ray photoelectron spectroscopy (XPS) curves of C1s for the catalyst material of Comparative Example 1 (Image A) and the catalyst material of Example 1 (Image B). [Diagram 3] 1 shows deconvoluted XPS curves of Pt4f in the catalyst material of Comparative Example 1 (Image A) and the catalyst material of Example 1 (Image B). [Figure 4] Figure 4A shows a plot of current density versus cell potential v from half-cell tests performed with gas diffusion electrodes containing the catalytic material of Comparative Example 1 and with gas diffusion electrodes containing the catalytic materials of Examples 1-4. Figure 4B shows a plot of mass activity versus cell potential v from half-cell tests performed with a gas diffusion electrode containing the catalytic material of Comparative Example 1 and with gas diffusion electrodes containing the catalytic materials of Examples 1-4 using a pure oxygen feed. [Diagram 5]5A is a bar graph showing the mass activity determined from half-cell testing for gas diffusion electrodes containing the catalytic material of Comparative Example 1 and the catalytic materials of Examples 1 to 4. FIG 5B is a bar graph showing the specific activity determined from half-cell testing for gas diffusion electrodes containing the catalytic material of Comparative Example 1 and the catalytic materials of Examples 1 to 4. [Figure 6] FIG. 6A shows a plot of current density vs. cell potential v from a single cell test performed on a membrane electrode assembly containing the catalyst material of Comparative Example 1 and a membrane electrode assembly containing the catalyst material of Example 1, corrected for internal resistance. Pure oxygen was supplied to the cathode. FIG. 6B shows a plot of current density vs. potential v from a single cell test performed on a membrane electrode assembly containing the catalyst material of Comparative Example 1 and a membrane electrode assembly containing the catalyst material of Example 1, corrected for internal resistance. Air was supplied to the cathode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Preferred and / or optional features of the invention will now be described. Any aspect of the invention may be combined with any other aspect of the invention unless the context requires otherwise. Any preferred or optional feature of any aspect may be combined with any aspect of the invention, either singly or in any combination, unless the context requires otherwise. Reference to a catalytic material of the invention includes a catalytic material made by the method of the first aspect of the invention, as well as catalytic materials of the second and third aspects of the invention.
[0023] The catalytic material of the present invention comprises electrocatalyst particles, preferably nanoparticles. The exact electrocatalyst used will depend on the reaction it is intended to catalyze, and its selection is within the ability of one skilled in the art. The electrocatalyst may preferably be a cathode or anode electrocatalyst of a fuel cell, more preferably a proton exchange membrane fuel cell. The electrocatalyst is suitably: (i) the platinum group metals (platinum, palladium, rhodium, ruthenium, iridium, and osmium); (ii) gold or silver; (iii) base metals; or an alloy or mixture containing one or more of these metals or their oxides. The base metal is a transition metal that is not tin or a noble metal. The noble metal is a platinum group metal (platinum, palladium, rhodium, ruthenium, iridium or osmium) or gold. Preferred base metals are copper, cobalt, nickel, zinc, iron, titanium, molybdenum, vanadium, manganese, niobium, tantalum, chromium, and tin.
[0024] Typically, the electrocatalyst comprises, preferably consists essentially of, more preferably consists of (or comprises only) a platinum group metal or an alloy of a platinum group metal, preferably with a base metal (preferred base metals as defined above). In particular, the electrocatalyst comprises, preferably consists essentially of, more preferably consists of (or comprises only) platinum or an alloy of platinum with a base metal (preferred base metals as defined above), preferably nickel or cobalt, most preferably nickel. The atomic ratio of platinum to the alloying metal is typically in the range of, inclusive, 3:1 to 1:3.
[0025] The electrocatalyst is dispersed on a support material. It is therefore a supported electrocatalyst, and the term "supported" will be readily understood by those skilled in the art. For example, the term "supported" will be understood to include electrocatalysts that are bound or fixed to a support material by physical or chemical bonds. For example, the electrocatalyst may be bound or fixed to a support material by ionic or covalent bonds, or non-specific interactions such as van der Waals forces.
[0026] Preferably, electrically conductive carbon support materials are used, preferably in powder form.The carbon support material can be, for example, commercially available carbon black (e.g., from Cabot Corp. (Vulcan® XC72R)), or Akzo Nobel (Ketjen® Black Series), or graphitized versions of these carbon blacks or other commercially available carbon blacks such as acetylene black (e.g., those available from Chevron Phillips (Shawinigan Black®) or Denka).The support material can also be specially designed for use in fuel cells, such as those described in WO2013 / 045894.
[0027] Alternatively, the support material may be a metal oxide or mixed oxide, in particular a conductive mixed oxide such as niobia-doped titania, phosphorus-doped tin oxide and mixed platinum-based metal oxides or mixed metal oxides (as disclosed in WO 2012 / 080726), a carbide (e.g. tungsten carbide, molybdenum carbide or titanium carbide, preferably tungsten carbide or titanium carbide), a nitride, in particular a conductive nitride (e.g. titanium nitride or titanium aluminium nitride).
[0028] The electrocatalyst loading in the catalyst material and catalyst material precursor can be expressed in terms of weight percent active metal, e.g., platinum group metal, in the electrocatalyst, based on the total weight of the electrocatalyst and support material (i.e., excluding any other materials, including graphitic carbon nitride present), which can be determined using inductively coupled plasma mass spectrometry (ICPMS). Thus, the loading can suitably be at least 10 wt.% active metal, e.g., platinum group metal. The electrocatalyst loading can suitably be 90 wt.% or less active metal, e.g., platinum group metal, typically 60 wt.% or less active metal, e.g., platinum group metal, for example 40 wt.% or less active metal, e.g., platinum group metal, based on the total weight of the electrocatalyst and support material.
[0029] Graphitic carbon nitride, also denoted g-C3N4, is a known and well-studied graphitic layered material composed of regular tri-s-triazine or heptazine subunits connected via planar tertiary amino groups within the layers and weak van der Waals forces between the layers. Graphitic carbon nitride is made by condensation of precursor compounds, assisted by sonication and / or heating, including, for example, melamine, dicyandiamide, cyanamide, urea, thiourea, and ammonium thiocyanate. Condensation proceeds through polymeric C3N4 structures, called melons, which further condense into graphitic carbon nitride with tri-s-triazine units as the basic building blocks.
[0030] In the present invention, step (ii) may be performed by contacting the catalyst material precursor with a graphitic carbon nitride precursor compound, preferably a solution of the compound, and applying conditions sufficient to convert, preferably condense (i.e., convert by condensation reaction) the graphitic carbon nitride precursor to graphitic carbon nitride. Suitably, the graphitic carbon nitride is applied to the catalyst material precursor by mixing the catalyst material precursor with a solution of the desired graphitic carbon nitride precursor, preferably melamine, dicyandiamide, or cyanamide, more preferably cyanamide, e.g., water. Preferably, the mixture is sonicated to ensure that the catalyst material precursor is well dispersed in the solution of graphitic carbon nitride. Most preferably, the catalyst material precursor is mixed with a solution of cyanamide in water. The concentration of the graphitic carbon nitride precursor in the solution is not particularly limited and may be, for example, 50% by weight, inclusive, for example, in the range of 25-75% by weight. Those skilled in the art will be aware of conditions sufficient to condense the graphitic carbon nitride precursor to form graphitic carbon nitride. The mixture is preferably dried and then calcined, preferably in an inert atmosphere, e.g. argon atmosphere, at a temperature in the range and inclusive of 250-750°C, preferably 400-600°C, for a time at the required temperature, preferably not more than 10 hours, preferably not more than 5 hours. The mixture is preferably calcined at the required temperature for at least 1 hour. The drying step may be carried out, for example, by leaving the mixture in air for a period of at least 12 hours and not more than 48 hours, preferably not more than 36 hours or not more than 24 hours. However, the skilled person will be aware of how to carry out the drying step. The graphitic carbon nitride in the catalyst material of the present invention is preferably bonded to the support material by a covalent bond, and as such, the method of the present invention preferably results in a covalent bond between the graphitic carbon nitride and the support material. Such covalent bonds may be detected, for example, by X-ray photoelectron spectroscopy, as shown in FIG. 2 and described in the Examples section.
[0031] The loading of graphitic carbon nitride is preferably 5% by weight or less, preferably 3.5% by weight or less, more preferably less than 2% by weight, based on the total weight of graphitic carbon nitride and support material (i.e. excluding any other materials, including electrocatalyst, present). The loading of graphitic carbon nitride is preferably at least 0.5% by weight, based on the total weight of graphitic carbon nitride and support material. Those skilled in the art will recognize methods that can be used to determine the elemental composition of a sample and to determine the amount of graphitic carbon nitride in such catalytic materials. For example, the loading can be determined by conventional techniques such as combusting the sample and analyzing the product gas (i.e., combustion analysis), for example, using a CHNS / O analyzer (e.g., Perkin-Elmer 2400 series) based on a molar ratio of C to N=3:4. In this way, the total N content can be determined, and then the content of carbon as graphitic carbon nitride can be calculated based on a molar ratio of C to N=3:4, and then the weight of graphitic carbon nitride can be determined. The loading can be controlled by controlling the amount of graphitic carbon nitride precursor used in the process of the present invention.
[0032] The graphitic carbon nitride is preferably uniformly distributed on the surface of the catalytic material. The graphitic nitride is preferably distributed on at least 80%, preferably at least 90%, more preferably at least 95% of the free surface of the support material, i.e., on the surface of the support material not containing the electrocatalyst. The presence of uniformly distributed nitrogen on the catalytic material can be confirmed by energy dispersive X-ray spectroscopy (EDS) elemental mapping of transmission electron microscope (TEM) images, as shown in Figure 1. The formation of graphitic carbon nitride on the catalytic material can be detected by X-ray analysis, for example, as shown in Figure 2, and explained in the Examples section.
[0033] The electrocatalyst layer of the present invention can be preferably a cathode or an anode of a fuel cell, more preferably a proton exchange membrane fuel cell. The properties of the electrocatalyst layer, such as thickness, electrocatalyst loading, porosity, pore size distribution, average pore size, and hydrophobicity, depend on whether it is used in the anode or the cathode. In particular, the electrocatalyst layer is used in the cathode. In the anode, the thickness of the electrocatalyst layer is preferably at least 1 μm, typically at least 5 μm. In the anode, the thickness of the electrocatalyst layer is preferably 15 μm or less, typically 10 μm or less. In the cathode, the thickness of the electrocatalyst layer is preferably at least 2 μm, typically at least 5 μm. In the cathode, the thickness of the electrocatalyst layer is preferably 20 μm or less, typically 15 μm or less.
[0034] The electrocatalyst loading in the electrocatalyst layer will also depend on the intended use. In this context, electrocatalyst loading refers to the amount of active metal, e.g., platinum group metal, in the electrocatalyst layer. Thus, when the electrocatalyst is an alloy of platinum, the electrocatalyst loading is expressed in mg / cm. 2 For example, in a fuel cell cathode containing a platinum-containing electrocatalyst, the electrocatalyst loading is preferably at least 0.05 mg Pt / cm 2 , e.g., 0.5 mgPt / cm 2 Less than 0.3 mgPt / cm 2 In the fuel cell anode, the electrocatalyst loading is preferably at least 0.02 mg Pt / cm 2 , e.g., 0.2 mg / Ptcm 2 Less than or equal to 0.15 mgPt / cm 2 The following is the result.
[0035] The electrocatalyst layer of the present invention preferably comprises an ion-conducting polymer, such as a proton-conducting polymer, to improve the ionic conductivity of the layer. Thus, the ion-conducting material may comprise an ionomer, such as a perfluorosulfonic acid material (e.g., Nafion® (Chemours Company), Aciplex® (Asahi Kasei), Aquivion® (Solvay Specialty Polymer), Flemion® (Asahi Glass Co.)), or an ionomer based on partially fluorinated or non-fluorinated hydrocarbons that are sulfonated or phosphonated polymers, such as fumapem® P, E or K series products from FuMA-Tech GmbH, those available from JSR Corporation, Toyobo Corporation, etc. Preferably, the ionomer is a perfluorosulfonic acid, particularly the Nafion® series available from Chemours, especially Nafion® 1100EW, and the Aquivion® series available from Solvay, especially Solvay® 830EW.
[0036] The electrocatalyst layer of the present invention may include additional components. Such components include, but are not limited to, an oxygen generation catalyst, a hydrogen peroxide decomposition catalyst, a hydrophobic additive (e.g., a polymer such as polytetrafluoroethylene (PTFE) or an inorganic solid, with or without a surface treatment) or a hydrophilic additive (e.g., a polymer or an inorganic solid, such as an oxide) to control reactant and water transport properties. The selection of the additional components depends on whether the electrocatalyst layer is used in the anode or cathode, and it is within the ability of a person skilled in the art to determine which additional components are appropriate.
[0037] To prepare the electrocatalyst layer, the catalyst material of the present invention and any additional components are dispersed in aqueous and / or organic solvent to prepare the catalyst ink. If necessary, particle breakage is performed to achieve a suitable particle size distribution by methods known in the art, such as high shear mixing, milling, ball milling, passing through a microfluidizer, or the like, or combinations thereof. After preparation of the catalyst ink, the ink is deposited on a substrate (e.g., a gas diffusion layer, an ion-conducting membrane, or a carrier / transfer substrate) to form the electrocatalyst layer. The ink may be deposited by any suitable technique known in the art, including, but not limited to, gravure coating, slot die (slot, extrusion) coating, screen printing, rotary screen printing, inkjet printing, spraying, painting, gap coating techniques such as bar coating, pad coating, knife or doctor blade over roll, and application of a metering rod.
[0038] An electrocatalyst layer may be deposited on the gas diffusion layer to form the gas diffusion electrode of the present invention. The gas diffusion layer comprises a gas diffusion substrate and, preferably, a microporous layer. When the microporous layer is present, the electrocatalyst layer is deposited on the microporous layer. Typical gas diffusion substrates include nonwoven papers or webs comprising a network of carbon fibers and a thermosetting resin binder (e.g., TGP-H series of carbon fiber papers available from Toray Industries Inc., Japan, or H2315 series available from Freudenberg FCCT KG, Germany, or Sigracet series available from SGL Technologies GmbH, Germany, or AvCarb series from Ballard Power Systems Inc.), or woven carbon cloth. The carbon paper, web, or cloth may be pretreated prior to the fabrication of the electrode and incorporated into the membrane electrode assembly to make it either more wettable (hydrophilic) or more resistant to wettability (hydrophobic). The nature of any treatments will depend on the type of fuel cell and the operating conditions used. The substrate can be made more wettable by incorporating materials such as amorphous carbon black by impregnation from a liquid suspension, or made more hydrophobic by impregnating the pore structure of the substrate with a colloidal suspension of a polymer such as PTFE or polyfluoroethylenepropylene (FEP), followed by drying and heating above the melting point of the polymer. A typical microporous layer comprises a mixture of carbon black and a polymer such as polytetrafluoroethylene (PTFE).
[0039] In the catalyst coated ion conductive membrane of the present invention, an electrocatalyst layer is deposited on the ion conductive membrane, either by coating a catalyst ink directly on the membrane or by indirectly transferring it from a decal transfer substrate, to form the catalyst coated ion conductive membrane. The catalyst coated ion conductive membrane of the present invention may include a second electrocatalyst layer on its opposite side, which may be according to the present invention or other methods. The ion conductive membrane may suitably be any membrane suitable for use in a proton exchange membrane fuel cell, for example, the membrane may be based on perfluorinated sulfonic acid materials such as Nafion™ (Chemours Company), Aquivion™ (Solvay Specialty Polymers), Flemion™ (Asahi Glass Group), and Aciplex™ (Asahi Kasei Chemicals Corp.). Alternatively, the membrane may be based on sulfonated hydrocarbon membranes, such as those available as fumapem™ P, E, or K series products from FuMA-Tech GmbH, JSR Corporation, Toyobo Corporation, and other companies.
[0040] The thickness of the ion-conductive membrane is not particularly limited and will depend on the intended use of the ion-conductive membrane. For example, a typical fuel cell ion-conductive membrane has a thickness of at least 5 μm, preferably at least 8 μm, and preferably at least 10 μm. A typical fuel cell ion-conductive membrane has a thickness of 50 μm or less, preferably 30 μm or less, and preferably 20 μm or less. Thus, a typical fuel cell ion-conductive membrane has a thickness in the range of 5 to 50 μm, preferably 8 to 30 μm, and preferably 10 to 20 μm.
[0041] The ion conducting membrane may include additional components such as a peroxide decomposition catalyst and / or a radical decomposition catalyst, and / or a recombination catalyst. The recombination catalyst catalyzes the recombination of unreacted H2 and O2, which can diffuse from the anode and cathode of the fuel cell, respectively, into the ion conducting membrane to produce water. The ion conducting membrane may also include a reinforcing material, such as a planar porous material (e.g., expanded polytetrafluoroethylene (ePTFE) as described in USRE37307), embedded within the thickness of the ion conducting membrane to provide improved ion conducting membrane strength, such as increased tear resistance and reduced dimensional change upon hydration and dehydration, thus further extending the durability of the membrane electrode assembly and the life of the fuel cell incorporating the catalytic ion conducting membrane of the present invention. Other approaches to forming reinforced ion-conducting membranes include those disclosed in U.S. Patent Nos. 7,807,063 and 7,867,669, where the reinforcement is a rigid polymer film, such as a polyimide, in which a number of pores are formed and then filled with a PFSA ionomer. Graphene particles dispersed in an ion-conducting polymer layer may also be used as a reinforcement material.
[0042] Any reinforcement present may extend across the entire thickness of the ion conductive membrane or may extend only a portion of the thickness of the ion conductive membrane. It will be understood that the thickness of the ion conductive membrane extends perpendicular to the plane of the ion conductive membrane, e.g., in the z-direction of the penetration plane. It may be further advantageous to reinforce the periphery of the first and second surfaces of the ion conductive membrane to a greater extent than the central plane of the first and second surfaces of the ion conductive membrane. Conversely, it may be desirable to reinforce the center of the first or second surface of the ion conductive membrane to a greater extent than the periphery of the first or second surface of the ion conductive membrane.
[0043] The catalyst ink is coated on the decal transfer substrate to deposit the electrocatalyst layer on the decal transfer substrate, forming the catalyst decal transfer substrate of the present invention. Prior to removal of the decal transfer substrate, additional layers may be deposited on the exposed surface of the electrocatalyst layer, for example, an ion-conducting ionomer layer may be applied from an ionomer dispersion using any suitable deposition technique known as described above with respect to the deposition of the electrocatalyst layer. Further additional layers may be added as needed, for example, as described in PCT Publication WO2015 / 145128. The decal transfer substrate is removed from the electrocatalyst layer at an appropriate time. The decal transfer substrate may be formed from any suitable material that may be removed without damaging the electrocatalyst layer. Examples of suitable materials include fluoropolymers such as polytetrafluoroethylene (PTFE), ethylene tetrafluoroethylene (ETFE), perfluoroalkoxy polymer (PFA), fluorinated ethylene propylene (FEP - a copolymer of hexafluoropropylene and tetrafluoroethylene) and polyolefins such as oriented polypropylene (BOPP).
[0044] As will be appreciated by those skilled in the art, the membrane electrode assembly of the present invention can be constructed by many methods when it contains at least one electrocatalyst layer of the present invention. For example, the membrane electrode assembly can include an ion-conducting membrane of the present invention that includes two electrocatalyst layers, at least one of which is an electrocatalyst layer of the present invention, and a gas diffusion layer is applied to each electrocatalyst layer. Alternatively, the membrane electrode assembly can include an ion-conducting membrane sandwiched between two gas diffusion electrodes, and at least one gas diffusion electrode is a gas diffusion electrode of the present invention. The membrane electrode assembly can also include a catalyst-coated ion-conducting membrane with one electrocatalyst layer and a gas diffusion electrode on the opposite side of the ion-conducting membrane, and either or both of the electrocatalyst layer and the gas diffusion electrode are of the present invention.
[0045] The fuel cell of the present invention is preferably a proton exchange membrane fuel cell.
[0046] Working Example Preparation of catalytic materials Example 1: Platinum electrocatalyst (20 wt%), g-C3N4 (0.75 wt%) on a carbon black support (Vulcan® XC72R).
[0047] Example 2: Platinum electrocatalyst (20 wt%), g-C3N4 (1.4 wt%) on carbon black support (Vulcan® XC72R).
[0048] Example 3: Platinum electrocatalyst (20 wt%), g-C3N4 (1.9 wt%) on carbon black support (Vulcan® XC72R).
[0049] Example 4: Platinum electrocatalyst (20 wt%), g-C3N4 (3.1 wt%) on carbon black support (Vulcan® XC72R).
[0050] Comparative Example 1: Platinum electrocatalyst (20 wt %) on a carbon black support (Vulcan® XC72R). g-C3N4=graphitic carbon nitride.
[0051] For platinum electrocatalysts, the weight percentages given are based on the combined weight of the platinum electrocatalyst and the carbon black support. For graphitic carbon nitride, the weight percentages given are based on the combined weight of the graphitic carbon nitride and the carbon black support.
[0052] For Examples 1-4, samples of g-C3N4 with Pt(20 wt%) NP / VC (g-C3N4=graphitic carbon nitride, NP=nanoparticles, VC=Vulcan® XC72R carbon powder from Cabot Corporation) were synthesized using Pt(20 wt%) NP / VC as the catalyst material precursor and cyanamide (50 wt% in H2O, Sigma-Aldrich) as the graphitic carbon nitride precursor. For Example 1, 100 mg of Pt(20 wt%) NP / VC was mixed with 0.1 mL of cyanamide solution and 9.9 mL of H2O and sonicated for 20 min. After storing overnight at ambient conditions, the mixture was left in air to dry and then heated at 550 °C in Ar for 3 h to produce g-C3N4 with Pt(20 wt%) NP / VC. For the synthesis of Examples 2, 3, and 4, 0.2 mL, 0.3 mL, and 0.5 mL of cyanamide solution were used, respectively.
[0053] Comparative Example 1 is the same catalyst material precursor used to prepare Examples 1-4, Pt(20 wt %) NP / VC.
[0054] Pt(20 wt%) NP / VC is a particulate carbon-supported nanoparticle material made using a method similar to the general method for making carbon-supported catalysts described in WO 2013 / 045894 using Vulcan® XC72R carbon powder from Cabot Corporation.
[0055] Material characterization Scanning electron microscopy (SEM) images were obtained using an FEI Helios NanoLab 650 FIB (focused ion beam)-SEM.
[0056] Energy dispersive X-ray spectroscopy (EDS) elemental mapping and transmission electron microscopy (TEM) imaging were performed using an FEI Tecnai G2 microscope operated at 200 kV.
[0057] The amounts of C and N were determined by combustion analysis using a CHNS / O analyzer (Perkin-Elmer 2400 series), and the content of g-C3N4 in the samples was calculated based on the molar ratio of C to N = 3:4.
[0058] X-ray photoelectron spectroscopy (XPS) analyses were performed on a Leybold MAX200 spectrometer using a MgKα source (1253.6 eV) operated at 15 kV and 20 mA. All binding energies were corrected for sample charging by referencing the arbitrary C1s peak at 285.0 eV.
[0059] Electrochemical measurements half battery measurement An electrochemical half-cell operated with a gaseous oxygen feed was used to evaluate the electrocatalytic activity of the catalytic materials. The cell was capable of producing high current densities (approximately 2 A cm -2 ), thus allowing the user to mimic a practical fuel cell operating environment.
[0060] The components and setup of the half-cell are described in B. Pinaud, et al. Key considerations for high current fuel cell catalyst testing in an electrochemical half-cell, J. Electrochem. Soc., 2017, 164, F321-F327. Briefly, a large platinum gauze (52 mesh, 99.9%, Alfa Aesar) and a platinum wire (0.5 mm diameter, 99.95%, Alfa Aesar) were utilized to fabricate a flag counter electrode with a high surface area. A Hg / Hg2SO4 (filled with 0.5 M H2SO4 solution) electrode was used as the reference electrode. A catalyst-coated gas diffusion electrode with a microporous layer (Sigracet 29BC) was used as the working electrode, which has a surface area of 1.91 cm 2 The exposed active surface area of the working electrode is 0.1 mg Pt cm. -2The electrochemical potential was set as 0.05 V and the actual electrocatalyst loading was determined by ICP-OES analysis. The electrolyte consisted of 1 M perchloric acid (HClO4). All half-cell measurements were performed at ambient temperature (approximately 20 °C) to minimize safety risks associated with hot HClO4 and to prevent loss of electrolyte due to evaporation. Glass frits (Ace sparger tubes, porosity D, Sigma-Aldrich) were used to purge the cell electrolyte and headspace with either Ar or O2. All gases were delivered at a pressure of 1 atm (101 kPa (absolute)) and had a purity of 99.99% or higher. A potentiostat (5A board, Bio-Logic VMP3) was used for potential control and data acquisition. The reference electrode was routinely calibrated to a reversible hydrogen electrode (RHE) at each electrolyte concentration and all potentials are reported on the RHE scale unless otherwise specified.
[0061] Mass activity (mA / mg) shown in FIG. Pt ) data were taken directly from Figure 4B at various cell potentials (i.e., 0.80, 0.85, 0.90 V). Mass activity was measured in the low current density region (0–100 mA / cm) shown in Figure 4A. 2 For the calculation, the catalyst-coated gas diffusion electrode for the half-cell test was 1.91 cm 2 In addition, the actual Pt loading in the catalyst-coated gas diffusion electrode was determined by ICP-OES. Based on these parameters, the current density (mA / cm) shown in FIG. 4A was calculated. 2 ) is the mass activity (mA / mg) shown in FIG. Pt ) can be easily converted to the specific activity data (mA / cm) shown in FIG. 2 ) data are the electrochemical surface area (ECSA, cm) of each catalytic material. 2 / mg Pt ) divided by the mass activity (mA / mg Pt ) data. The electrochemical surface area (ECSA) is 0.21 mC cm on polycrystalline platinum.-2 was determined from the integrated charge in the hydrogen adsorption region of the steady-state CV curve (after subtraction of the capacitance contribution). Cyclic voltammogram (CV) measurements were performed at room temperature in Ar-purged 0.1 M HClO4 at 20 mV s -1 All cyclic voltammograms (CVs) were 100% IR-corrected (in situ compensation 95% and post-processing 5%) by measuring the resistance in an open circuit at f = 10 kHz. Details of the IR correction procedure for galvanostatic polarization curves are described in reference B. Pinaud, et al. Key considerations for high current fuel cell catalyst testing in an electrochemical half-cell, J. Electrochem. Soc., 2017, 164, F321-F327.
[0062] Single cell measurement 50cm 2 Total area of 14cm 2 A membrane electrode assembly with an active area of 0.16 mg / cm2 was fabricated by applying a cathode gas diffusion electrode and an anode gas diffusion electrode to either side of a perfluorosulphonic acid (PFSA) reinforced membrane. The non-active areas were masked. The cathode gas diffusion electrode was fabricated by applying 0.16 mg / cm2 of PFSA ionomer in a catalyst layer on a gas diffusion layer of Sigracet 29BC. 2 The anode gas diffusion electrode contained the catalyst materials of the examples and comparative examples with a platinum loading of 0.04 mg / cm in a catalyst layer with PFSA ionomer on a gas diffusion layer of Sigracet 29BC. 2 The anode electrocatalyst included an anode electrode catalyst (HiSPEC® 3000 with a nominal platinum loading of 20 wt % on a carbon support) with a loading of 100%.
[0063] For single cell measurements, 50cm 2 Screener Cell operated at 100% relative humidity on both the anode and cathode, and a 14 cm2 The larger area was masked. The anode was fed with H2 (stoichiometry 1.5) and the cathode with O2 or air (stoichiometry 2). The cell temperature was 80°C, the cell compression was 80 psi, and the cell gas pressure was 150 kPa for the anode and cathode.
[0064] Results and Discussion FIG. 1 shows the location of platinum (Images D and E) and nitrogen (Images C and E) in the catalyst material of Example 1 after deposition of graphitic carbon nitride using EDS elemental mapping. The data showed that the nitrogen, and thus the graphitic carbon nitride, is uniformly distributed on the catalyst material. In the original data, nitrogen is represented in green and platinum is represented in red. The original data shows a uniform distribution of green and red on the carbon support material.
[0065] The deconvoluted XPS curves in Figure 2 show that new C=O and graphitic carbon nitride CNC bonds were generated after the application of graphitic carbon nitride. Figure 2A is the data from the catalyst material of Comparative Example 1, and Figure 2B is the data from the catalyst material of Example 1. It is therefore clear that the method of the present invention results in the presence of graphitic carbon nitride, which is covalently bonded to the support material.
[0066] The deconvoluted XPS curves in FIG. 3 show that the predominant platinum species is Pt(0) for both the catalytic material of Comparative Example 1 (FIG. 3A) and the catalytic material of Example 1 (FIG. 3B). Specifically, the percentage of each Pt species (i.e., Pt(0), Pt(II) and Pt(IV)) in the samples can be calculated according to the area surrounded by the peaks of Pt(0), Pt(II) and Pt(IV). The predominant platinum species is Pt(0) (not Pt(II) or Pt(IV)) for both samples, meaning that the method of the present invention does not change the nature of the platinum electrocatalyst. This is advantageous because, for example, if the predominant platinum species were to change from Pt(0) to Pt(II) or Pt(IV), the electrocatalytic activity of the electrocatalyst could be significantly reduced.
[0067] The polarization and mass activity curves determined in half-cells shown in Figures 4A and 4B, respectively, show that maximum graphitic carbon nitride is present to make the catalytic materials of Examples 1-4 perform better than the catalytic material of Comparative Example 1. At high current densities, loadings of less than 2 wt. % (i.e., Examples 1 and 2) relative to the total weight of the graphitic carbon nitride and carbon black support result in better electrochemical performance than the catalytic material of Comparative Example 1. The mass activity and specific activity data in Figures 5A and 5B show similar trends.
[0068] The polarization curves of the single cell test of the catalytic materials of Comparative Example 1 and Example 1 shown in Figures 6A and 6B show a surprising increase in the electrochemical performance of the catalytic materials of the present invention when compared to conventional catalytic materials. The increase in performance seen under O2 shown in Figure 6A (where the reaction is under kinetic control) indicates an increase in the catalytic activity of the catalytic materials of the present invention themselves. In Figure 6B under air, this increased catalytic activity is evident at low current densities, whereby kinetic control still prevails.
Claims
1. 1. A method of making a catalytic material comprising electrocatalyst particles, an electrically conductive carbon support material, and a graphitic carbon nitride, the method comprising: (i) providing a catalyst material precursor comprising electrocatalyst particles dispersed on an electrically conductive carbon support material; and then (ii) applying graphitic carbon nitride to the catalytic material precursor provided in step (i); the catalytic material precursor does not include graphitic carbon nitride; The method wherein the electrocatalyst comprises a platinum group metal or an alloy of a platinum group metal.
2. 2. The method of claim 1, wherein the catalytic material comprises up to 5 weight percent graphitic carbon nitride, based on the total weight of the graphitic carbon nitride and the support material.
3. 3. The method of claim 1 or 2, wherein step (ii) is carried out by contacting the catalytic material precursor with a graphitic carbon nitride precursor compound and applying conditions sufficient to convert the graphitic carbon nitride precursor to graphitic carbon nitride.
4. 1. A catalytic material comprising electrocatalyst particles, an electrically conductive carbon support material, and graphitic carbon nitride dispersed on a surface of the electrically conductive carbon support material, wherein the electrocatalyst particles are dispersed on the electrically conductive carbon support material, the catalytic material comprises 5 wt.% or less graphitic carbon nitride based on a total weight of the graphitic carbon nitride and the electrically conductive carbon support material, and the electrocatalyst particles comprise a platinum group metal or an alloy of a platinum group metal.
5. An electrocatalyst layer comprising the catalytic material of claim 4 .
6. A catalyst coated ion conductive membrane comprising the electrode catalyst layer according to claim 5 and an ion conductive membrane.
7. A gas diffusion electrode comprising the electrode catalyst layer according to claim 5 and a gas diffusion layer.
8. A membrane electrode assembly comprising the electrode catalyst layer according to claim 5, the catalyst coated ion conductive membrane according to claim 6, or the gas diffusion electrode according to claim 7.
9. A fuel cell comprising the electrode catalyst layer according to claim 5, the catalyst coated ion conductive membrane according to claim 6, the gas diffusion electrode according to claim 7, or the membrane electrode assembly according to claim 8.
10. 10. The fuel cell of claim 9, wherein the fuel cell is a proton exchange membrane fuel cell.
11. A catalyst decal transfer substrate comprising the electrode catalyst layer according to claim 5 and a decal transfer substrate.
Citation Information
Patent Citations
Preparation method and application of carbon material modified graphite phase carbon nitride nanosheet loaded platinum nano electrocatalyst
CN111129510A
Partially graphitized carbon nitride loaded noble metal material and preparation method and application thereof
CN114534765A
Fuel cell membrane
JP2005539352A
Catalyst for fuel cell electrode
JP2007175578A
Electrode catalyst
JP2019029304A